6 new students selected for Mygift education incentive - UMP, PNC (2018)
Kuantan, 2 September – It’s like a dream come true. That is what Mugunthan A/L Krishnan felt when he get the offer to further his study at Faculty of Chemical & Natural Resources Engineering in UMP.